Assessment of genetic divergence in pumpkin (Cucurbita moschata) - Arya, POOJA; MAURYA, S K (The Indian Journal of Agricultural Sciences, 2022)
Pumpkin (Cucurbita moschata L.) is one of the most important Cucurbitaceous crops having a huge potential of nutritional security and has vast diversity in Indian condition. Forty diverse genotypes of pumpkin were evaluated for phenotypical variations and assessment of genetic diversity, at G B Pant University of Agriculture and Technology Pantnagar during spring-summer of 2018 and 2019. The experiment was laid out in Randomized Block Design (RBD) with three replications. The data was subjected to Principal Component Analysis, where a total of 8 components were identified. First four components account for about 60.26% and 60.33% cumulative effects during first and second season, respectively. During first year the Eigen root of the first principal component caused 20.24% variation of total variation while, during second year the Eigen root of first principal component accounted 25.58% variation of total variation. A relative positive weight by each of the component to each single trait indicated that there was great scope for improvement in these traits through selection. Presence of sufficient phenotypic and genotypic diversity showed the scope in pumpkin crop for further improvement.